Dampak kreativitas, inovasi dan strategi harga terhadap kinerja usaha mikro serta kecil - Jatenangan Manalu (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study aims to determine the effect of creativity and innovation on SMEs' performance. Moreover, this study examines the moderating role of pricing strategies on the relationship between creativity and innovation on SME performance. The data was collected by distributing questionnaires using hard copy (offline) or via google form (online) from 145 SME businesses. As expected, creativity is positively related to innovation behavior and SME performance. The results also provide convincing empirical support regarding the positive role of pricing strategies in improving performance through creativity. This study provides new insights into the more complex relationship between creativity, innovation, and SME performance.